Impact of moderate to severe mitral stenosis in patients undergoing transcatheter aortic valve replacement. (1st July 2019) - Fischer, Quentin; Himbert, Dominique; Bernier, Mathieu; Urena, Marina; Nunes Ferreira-Neto, Alfredo; Paradis, Jean-Michel; Mohammadi, Siamak; Iung, Bernard; Rodés-Cabau, Josep
Abstract: Objective: In patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR), the impact of concomitant mitral stenosis (MS) remains unknown. The aim of this study was to determine the incidence and impact of moderate to severe MS in patients undergoing TAVR. Methods: The study included 2113 consecutive patients (mean age: 80 ± 9 years, mean STS: 6.4 ± 5.2%) who underwent TAVR in 2 centers. The presence of MS was defined as a mean transmitral gradient ≥ 5 mm Hg on baseline echocardiography in the absence of severe mitral regurgitation. Clinical events were prospectively collected in a dedicated TAVR database. Results: A total of 157 patients (7.4%) had moderate to severe MS (mean gradient: 7.2 ± 2.8 mm Hg; degenerative origin in 88%). Patients with MS were younger, more frequently women, had a higher left ventricular ejection fraction and an increased rate of severe pulmonary hypertension (p < 0.02 for all). Thirty-day mortality was similar in both groups (MS: 3.8%; no MS: 5.5%, adjusted p = 0.34). At a mean follow-up of 3 ± 2 years, there were no differences between groups in mortality (MS: 35%, no MS: 36.2%, adjusted HR: 1.14, 95% CI: 0.86–1.51), or heart failure rehospitalization (MS: 21%, no MS: 21.7%; adjusted HR: 1.16, 95% CI: 0.81–1.67). Patients with MS exhibited a similar functional status at follow-up compared to those with no MS (NYHA I–II in 85% and 88% of patients, respectively, adjusted p = 0.20). Conclusions: About 7% of patients undergoing TAVR had concomitant moderate to severe MS. The presence of MS had no negative impact on early and mid-term clinical outcomes post-TAVR. These results suggest that TAVR is a valid alternative for treating patients with aortic stenosis in the presence of moderate to severe MS. Highlights: About 7% of patients undergoing TAVR had concomitant moderate to severe MS. MS was not associated with poorer early and late outcomes in TAVR recipients. Similar improvements in functional status and exercise capacity were observed.